Proceso de atención de enfermería en paciente femenino de 32 años con colesteatoma de oído medio. - Chicaiza Almache, Aida Janeth (2021)
The present clinical case deals with a 32-year-old female patient with middle ear cholesteatoma who attended the Alfredo Noboa Montenegro Hospital accompanied by a relative (mother) due to vertigo, on the right ear, a dressing stained with serohematico fluid in the right retroauricular region and duct external auditory hearing, hearing loss, headache, earache, ringing, loss of balance, neck stiffness, presents retroauricular erythema affecting the mastoid region, crusted lesions and presence of an orifice with scarce odorous purulent discharge. The patient went to the hospital because the administration of unspecified medication did not provide expected results, intensifying the pain that does not allow her to carry out her activities normally. The main objective of the case is to execute the nursing care process, through the information of the patient in order to carry out adequate interventions that allow to improve the altered functional patterns. For which, physical, blood, radiography and audiometry studies were carried out that helped to provide adequate treatment in the patient consisting of: administration of paracetamol 1 g every 8 hours and IV tramadol to relieve pain, amoxicillin 500 mg three times a day, and ibuprofen 400mg every 6H, asepsis of the ears, extraction of seohematicos fluid and purulent secretions from the middle ear, surgical removal of the mastoid area cells; and after the postoperative period, ear cleaning, control of signs and support in the administration of medication.